COMMENTS ON NETER'S 'PROBLEMS IN EXPERIMENTING WITH THE APPLICATION OF STATISTICAL TECHNIQUES IN AUDITING' - Smith, C. D. (The Accounting Review, 1955)
Abstract This article focuses on problems in experimenting with the application of statistical techniques in auditing. In the first section of an article "Inadequacy of Some Experiments in the Past," published in the 1954 issue of the journal "Accounting Review," certain sample checks have been listed. The comment is that the reason for their lack of significance is that the experiments do not establish the relevance to the purpose of the audit, etc. This approach of working with an isolated phase of an audit was probably followed because it is much simpler than an attempt to tackle the audit as a whole. These statements indicate a misunderstanding of what was actually done. In the case of the a report the audit as a whole for the municipality was well established over a period of ten years before the case studies were begun. The purpose behind the report was to indicate how cases do occur during an audit where samples as a basis for judgment are both adequate and efficient. A report of this character should clarify something relative to the use of statistical methods in auditing.